2009
DOI: 10.1185/03007990902905468
|View full text |Cite
|
Sign up to set email alerts
|

Absenteeism and health-benefit costs among employees with MS

Abstract: Patients treated with 'A' reported significantly lower SL costs, SL days, and STD costs than patients treated with 'C', suggestive of greater real world benefits with 'A'. Despite small sample sizes and the retrospective nature, the study provides interesting insights into the use of DMTs in MS. The study also revealed important areas of future research, specifically the need for development of methods to determine which MS patient groups respond best to which DMT treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 28 publications
0
4
0
1
Order By: Relevance
“…Laut einer ähnlichen Studie besitzt auch der Persönlichkeitsfaktor "agreeableness" einen positiven prädiktiven Wert in Bezug auf den Erwerbsstatus [10]. Nur wenige Arbeiten haben sich bisher mit dieser konkreten Fragestellung beschäftigt: Eine kleine, retrospektive Untersuchung fand Hinweise für Unterschiede in der Anzahl an Fehltagen in Abhängigkeit des verwendeten Immunmodulators [28]. In einer anderen Arbeit zeigte sich ein positiver Effekt des untersuchten Immunmodulators sowohl auf die Fatigue als auch auf die Anzahl der Fehltage [29].…”
unclassified
“…Laut einer ähnlichen Studie besitzt auch der Persönlichkeitsfaktor "agreeableness" einen positiven prädiktiven Wert in Bezug auf den Erwerbsstatus [10]. Nur wenige Arbeiten haben sich bisher mit dieser konkreten Fragestellung beschäftigt: Eine kleine, retrospektive Untersuchung fand Hinweise für Unterschiede in der Anzahl an Fehltagen in Abhängigkeit des verwendeten Immunmodulators [28]. In einer anderen Arbeit zeigte sich ein positiver Effekt des untersuchten Immunmodulators sowohl auf die Fatigue als auch auf die Anzahl der Fehltage [29].…”
unclassified
“…Earlier studies indicated that both absenteeism and presenteeism were common among patients with MS,32 and loss of work productivity resulted from the substantial increase in the use of long- and short-term sick leave 33. In addition, employees with MS had more than four times the number of work loss days per year than controls,34 and the annual rates of absenteeism for employees with MS ranged from 3.0 to 8.1 days 35. Consistent with these previous studies, in the current study, absenteeism (3.3-fold), presenteeism (1.7-fold), overall work impairment (1.9-fold), and activity impairment (1.8-fold) were higher in patients with MS, compared with controls.…”
Section: Discussionmentioning
confidence: 99%
“…7,16,18,19 One such U.S. study of employees with MS and at least 1 DMT claim versus untreated employees with MS found that the risk-adjusted total annual medical costs ($4,393 vs. $6,187; P < 0.001) and indirect costs ($2,252 vs. $3,053; P < 0.001) were significantly lower for employees with at least 1 DMT claim. 43 With regard to differences between DMTs in MS-associated absenteeism, Brook et al (2009) found that patients receiving IM IFNβ-1a had lower sick-leave costs ($969 vs. $523, respectively; P = 0.047) and fewer sick-leave days (2.98 vs. 7.18 days, respectively; P = 0.01) versus those receiving GA. 81 Similarly, Rajagopalan et al (2011) reported that patients treated with IM IFNβ-1a demonstrated a significant improvement in the number of missed work days, with a decrease of 1.3 days (from 5.6 to 4.3 days) versus an increase of 2 days (from 2.3 to 4.3 days), in GA-treated patients (P < 0.05). 38 Only patients receiving IM IFNβ-1a showed a reduction in sick-leave absence days with therapy, while sick leave increased with SC IFNβ-1a, IFNβ-1b, and GA.…”
Section: Impact Of Dmts On Work Productivity and Absenteeismmentioning
confidence: 99%
“…In 1 study, annual absenteeism rates for employees with MS ranged from 2.98 to 8.13 days; total sick time ranged from 7.33 to 20.67 days; and sick-leave costs ranged from $523 to $1,431. 81 While the proportion of patients with MS in any given workforce will be low, those companies that do have employees with this illness may be affected by loss from reduced output while an employee is at work and from absenteeism as well as from extra staffing costs incurred to cover sick leave. 38,82 DMTs may allow employees to continue working and thus help reduce absenteeism.…”
Section: Cost-utility and Cost-effectiveness Analyses Of Dmtsmentioning
confidence: 99%
See 1 more Smart Citation